Becoming atomic: the bunker, modernity, and the city. Issue 3 (14th November 2018) - Boyd, Gary A.; Linehan, Denis
Abstract : From a starting point of Jay Swayze's extraordinary Underground Homes and Gardens project (1980) this paper explores and contextualises the bunker's significance and accelerated production under threat from atomic weapons in the Cold War. The nuclear bunker represents the end-point of a series of buried and semi-buried structures. Bulwarks since the early eighteenth century against increasingly sophisticated forms of ordnance, they emerge in increasing numbers throughout the twentieth century across a series of scales and spheres from the household to the civic and urban. In its proliferation as a building type and precise fitness to purpose, the bunker is arguably as emblematic of modernity as the department store, the great exhibition, the skyscraper or the machine-inspired domestic space advocated by Le Corbusier. It also represents the obverse – or perhaps a parodic iteration – of the preoccupations of early architectural modernism: a vast underground international style, cast in millions of tons of thick, reinforced concrete retaining walls, whose spatial relationship to the landscape above was strictly mediated through the periscope, the loop-hole, the range finder and the strategic necessity to both resist and facilitate the technologies and scopic regimes of weaponry. This paper critically uncoils Paul Virillo's observation that, once physically eclipsed in its topographical and technical settings, the bunker's efficacy would mutate to other domains, retaining and remaking its meaning in another topology. 'The essence of the new fortress', he writes, 'is elsewhere, underfoot, invisible from here on in'. Shaped by this impulse, this paper attempts to render visible the bunker's relationship to modernity and its architectural, cultural and urban contributions to the twentieth century. In doing so it excavates some of the relationships between the physical artefact, its implications and its enduring metaphorical and perceptual ghosts as domestic realms and whole cities and regions became atomic.